Validation of an adapted Italian-language version of the Sociocultural Attitudes Toward Appearance Questionnaire-3 (SATAQ-3), within a female population: the Sociocultural Attitudes Toward Appearance Questionnaire - Social Media (SATAQ-SM) - Riccardo, Anna Maria; Ferrazzi, Giulia; Catellani, Sara; Gibin, Anna Maria; Nasi, Anna Maria; Marchi, Mattia; Galeazzi, Gian Maria; Thompson, J. Kevin; Pingani, Luca (Frontiers in Psychology, 2024)
Sociocultural Attitudes Towards Appearance Questionnaire-Social Media (SATAQ-SM) is a self-administered questionnaire for the evaluation of social media pressure and internalization of beauty standards. This study aims to validate the SATAQ-SM an adapted Italian version of the Sociocultural Attitudes Towards Appearance Questionnaire third version (SATAQ-3). Confirmatory factor analysis was used to investigate whether the empirical data fitted the four-factor structure of SATAQ-3. Assessment of goodness-of-fit was based on standard model fit criteria: relative χ2 value (χ2/df), Root Mean-Squared Error of Approximation (RMSEA), Comparative Fit Index (CFI) and Tucker–Lewis Index (TLI). Internal consistency was assessed using McDonald’s omega. Criterion validity was calculated by correlating the SATAQ-SM factors scores with the total score of the Rosenberg self-esteem scale (RSES) and Eating Attitudes Test (EAT-26). Four-hundred and eighty-five females agreed to participate in the study. The four-factor model appears to be confirmed by the fit indices: χ2/df = 3.73, RMSEA = 0.07, CFI = 0.99 and TLI = 0.99. All the items defining the four factors had a factor loading of ≥0.40. McDonald’s omega of the entire questionnaire was equal to 0.95 and for the four subscales it did not assume values lower than 0.81. The correlations between the factor score of SATAQ-SM and the RSES were all negative and statistically relevant (p < 0.001); the correlations between the scores of the SATAQ-SM subscales and the total score of the EAT-26 are all positive and statistically significant. SATAQ-SM demonstrated good psychometric properties to assess the influence of social media on body image perception related to social media.